Net Zero Targets and GHG Emission Reduction in the UK and Norwegian Upstream Oil and Gas Industry: A Comparative Assessment - Hall, M (Oxford Institute for Energy Studies, 2020)
The recent adoption by the UK and Norway of net zero and climate neutrality targets by 2050 has galvanised the upstream oil and gas industry in both countries to adopt GHG emission reduction targets for 2030 and 2050 for the first time. Meeting these targets, ensuring an appropriate sharing of costs between investors and taxpayers and preserving investor confidence will present a lasting challenge to governments and industry, especially in periods of low oil and gas prices. The scale of the challenge on the Norwegian Continental Shelf (NCS) is far greater than on more mature UK Continental Shelf (UKCS) since the remaining resource base is much larger, the expected future production decline is less severe and the emission intensity on the NCS is already much lower (10 kg CO2e/boe) than on the UKCS (28 kgCO2e/boe) due to the long history of tighter emission standards and offshore CO2 taxation. Norway is expected to deliver future CO2 emission reduction through an extension of its existing powerfrom-shore investment programme. The high cost of such new investment, borne mainly by the state via the tax system, is a political and social choice made by Norway to reduce upstream CO2 emissions without giving up its commitment to develop its remaining resources of more than 50 bn boe and to preserve the source of its prosperity. In the UK upstream, the new industry target to reduce GHG emissions by 50 per cent by 2030 may demand less new capital but it will require the integration of emission abatement into the OGA’s MER UK strategy, well-designed economic incentives, including possibly carbon pricing and fiscal reform, and behavioural changes from operators. The relatively short remaining economic life of many mature fields and the dispersed nature of offshore power demand penalises both power-from-shore and CCS as routes to least-cost emission reduction but future integration with offshore renewable electricity generation may offer abatement opportunities at larger installations or new field developments. Methane emissions have for some years been a blind spot for government and industry on the UKCS, amounting to 1.6 mt CO2e in 2018, three times higher than on the NCS. The UKCS has the potential to reduce methane emissions significantly from flaring, venting and leakage through better emission reporting, a more robust consents regime and changes to operating practices.